PREDIKSI GAYA HUMOR TERHADAP KECENDERUNGAN SELF-COMPASSION PADA MAHASISWA - Ignatius Jonathan Kunardi; Ferdian, Flaviana Rinta (MANASA, 2024)
College students need effective coping strategies to optimize their performance and achieve their goals. One promising approach is self-compassion, which can help students navigate the challenges of college life. Self-compassion can be influenced by daily experiences, including humour style. Humour is often seen merely as a source of entertainment, but it can significantly impact self-compassion.This study examines the relationship between different humour styles and self-compassion. A total of 245 college students from various universities across Indonesia participated, selected through a convenience sampling method. The Humour Style Questionnaire and the Skala Welas Diri were used to measure humour styles and self-compassion, respectively. To analyze how different humour styles predict self-compassion, multiple regression analysis with the enter procedure was employed.The results showed that among the four humour styles (self-enhancing, affiliative, aggressive, and self-defeating), only self-enhancing, aggressive, and self-defeating humour significantly predicted self-compassion. Self-enhancing humour had the strongest predictive power, followed by aggressive humour and then self-defeating humour.